2020
DOI: 10.1002/cam4.2874
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sexual activity and sexual attitudes among breast cancer survivors in China

Abstract: PurposeLess is known about sexual attitudes of breast cancer survivors (BCSs) and its association with sexual activity and sexual dissatisfaction.MethodsWe investigated the proportion of sexual activity and sexual dissatisfaction in a cross‐sectional study among 341 Chinese BCSs aged 30‐75 years old, and we described their association with sexual attitudes, as well as socio‐demographic characteristics, physical health conditions, and mental health problems.ResultsOnly 83 (24.3%) individuals reported sexual act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Body image-related sexual activity scores ranked third in the dimensions scores 13.73 (3.67), and previous studies have shown that sexual activity is closely related to body image ( Sebri et al, 2021 ). On the one hand, surgery-induced scarring or mastectomy can lead to a variety of psychosocial problems, including reduced attraction and satisfaction with the body, decreased self-esteem and self-efficacy, and can adversely affect the sexual experience ( Yan et al, 2020 ). On the other hand, breasts are considered to be a symbol of femininity and image ( Smedsland et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Body image-related sexual activity scores ranked third in the dimensions scores 13.73 (3.67), and previous studies have shown that sexual activity is closely related to body image ( Sebri et al, 2021 ). On the one hand, surgery-induced scarring or mastectomy can lead to a variety of psychosocial problems, including reduced attraction and satisfaction with the body, decreased self-esteem and self-efficacy, and can adversely affect the sexual experience ( Yan et al, 2020 ). On the other hand, breasts are considered to be a symbol of femininity and image ( Smedsland et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… 15 Cultural differences in sexual health education needs are also apparent, as studies of Chinese patients with breast cancer have shown that they avoid sexual activity owing to perceptions that it may affect treatment outcomes and recurrence risk. 16 , 17 A multipronged approach to sexual health education may offer options suitable for a variety of needs.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in China in the year 2020, it was found that approximately 24.3% of BCSs reported engaging in sexual activity in the previous year. 39 Moreover, more than 50% of the BCSs believed that sexual activity could have an adverse impact on their disease recovery. Their attitudes toward sex included the perception that “sexual activity may hinder disease recovery.” 39 Considering the frequency of sexual activity, previous studies have found that BC and associated treatments often lead to a reduction in sexual desire along with a decrease in the frequency of engaging in sexual intercourse.…”
Section: Bodymentioning
confidence: 99%
“… 39 Moreover, more than 50% of the BCSs believed that sexual activity could have an adverse impact on their disease recovery. Their attitudes toward sex included the perception that “sexual activity may hinder disease recovery.” 39 Considering the frequency of sexual activity, previous studies have found that BC and associated treatments often lead to a reduction in sexual desire along with a decrease in the frequency of engaging in sexual intercourse. Reports from BC patients indicate that sexual disturbances can occur soon after diagnosis or even persist for years following treatment.…”
Section: Bodymentioning
confidence: 99%